Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1073/pnas.1211827110
|View full text |Cite
|
Sign up to set email alerts
|

Great majority of recombination events in Arabidopsis are gene conversion events

Abstract: The evolutionary importance of meiosis may not solely be associated with allelic shuffling caused by crossing-over but also have to do with its more immediate effects such as gene conversion. Although estimates of the crossing-over rate are often well resolved, the gene conversion rate is much less clear. In Arabidopsis, for example, nextgeneration sequencing approaches suggest that the two rates are about the same, which contrasts with indirect measures, these suggesting an excess of gene conversion. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
110
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(119 citation statements)
references
References 35 publications
8
110
1
Order By: Relevance
“…Lu et al (13) and Wijnker et al (12) sequenced the four products of, respectively, 2 and 13 pollen tetrads from a Columbia/Landsberg qrt1 F 1 and detected an average of only one to two NCO gene conversion events per meiosis, most of which included just a single marker. A subsequent reanalysis (44) of the Yang et al high-throughput sequencing data (43) led to the conclusion that many of the NCO gene conversions had arisen from misinterpretations of the short read sequence data and that the true number was much lower and consistent with other findings.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Lu et al (13) and Wijnker et al (12) sequenced the four products of, respectively, 2 and 13 pollen tetrads from a Columbia/Landsberg qrt1 F 1 and detected an average of only one to two NCO gene conversion events per meiosis, most of which included just a single marker. A subsequent reanalysis (44) of the Yang et al high-throughput sequencing data (43) led to the conclusion that many of the NCO gene conversions had arisen from misinterpretations of the short read sequence data and that the true number was much lower and consistent with other findings.…”
Section: Discussionsupporting
confidence: 48%
“…As discussed above, the degree of NCO gene conversion appears to be a function of the percent identity of the recombining sequences, so we can expect it to vary both at the gene level within a species and at the genome level between species. Another caveat in extrapolating genome-wide results from one species to another is that in some species, like Arabidopsis, most recombination events occur in intergenic regions (13,43,45), whereas in others, like maize, most recombination is intragenic (17,46). The latter observation is not surprising given the high degree of intergenic gross structural polymorphism in maize (36,47).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…thaliana (Yang et al, 2012), where they re-sequenced 40 F2 individuals from the A. thaliana lines Columbia and Landsberg erecta to compare the distribution of crossovers and gene conversions with the two parental individuals. This study identified more than 3000 gene conversions and 73 crossovers per plant.…”
Section: Durstewitz Et Al Identified 604 Snps Using 100 Est-based Ammentioning
confidence: 99%
“…The researchers removed all markers near putative duplicated regions to counter the errors introduced by mismapped reads. This way, they estimated 1-3 gene conversions and 10 crossovers per meiosis, a much smaller number than presented in (Yang et al, 2012). One of the limitations of most forms of genotyping, including RAD GBS, is that only a restricted set of the total SNPs are assayed across a population.…”
Section: Durstewitz Et Al Identified 604 Snps Using 100 Est-based Ammentioning
confidence: 99%